Skeletal Muscle Power Measurement in Older People: A Systematic Review of Testing Protocols and Adverse Events - Alcazar, Julian; Guadalupe-Grau, Amelia; García-García, Francisco J; Ara, Ignacio; Alegre, Luis M (The journals of gerontology. Series A, Biological sciences and medical sciences, 2018)
Muscle power has been proposed to be the primary therapeutic target for resistance training interventions aimed at enhancing physical function in older adults. However, no recommendations exist on ideal testing protocols to assess muscle power in older adults, and the safety of this procedure has not been adequately evaluated in the literature. A systematic review was conducted to identify studies evaluating muscle power exerted by older people in resistance exercises through May 2017. Information from muscle power testing protocols regarding familiarization, warm-up, measuring instrument, exercise, intensity, volume, rest intervals, data collection, and analysis was collected, as well as that regarding adverse events. Reporting bias was evaluated according to the recommendations given by the Cochrane Collaboration group. From 65 studies that met inclusion criteria, 3,484 older subjects and 11,841 muscle power tests distributed in 6,105 testing sessions were identified. A full description of the different muscle power testing protocols was conducted. In addition, a risk of adverse events of 0.15%-0.69% (one adverse event every 144-658 muscle power tests) was found. However, adverse events were poorly reported, with most of the studies showing a high risk of reporting bias. Major discrepancies were found in muscle power testing protocols among studies. This might limit consensus on designing optimal training programs to improve muscle power and physical function in older adults, and understanding the main mechanisms involved in the age-related loss of muscle power. Finally, muscle power testing was found to be safe in older people with a broad range of health and functional states.